PENGARUH LATIHAN ZIG-ZAG RUN TERHADAP PENINGKATAN KELINCAHAN SISWA PUTRA USIA 16-18 TAHUN - CANDRA DWI SATRIAPUTRA, GUSTI; WIDODO, ACHMAD (Jurnal Kesehatan Olahraga, 2019)
Agility is the ability of a person to be able to change direction quickly and precisely when moving without losing balance. Agility is one component of physical conditions that are very important to improve in sports, because many sports require agility. The purpose of this study is to knowing the effect oftraining zigzag run on increasing agility in male students aged 16-18 years. This research is experimental research using pre-test and post-test. The sample of this study was 15 populations. The results of this study obtained an average agility in the pre-test of 5.78 and in the post-test of 5.53. Based on the normality test of thedata pre-test obtained a significant level of 0.2 and thedata post-test obtained by the results of a significant level of 0.07 and the data are normally distributed, because thedata pre-test and post-test is greater than ? (0.2> 0.05 and 0.07> 0.05). Calculation of the test of the difference in average agility before and after based on statistical calculations using theformula paired sample t-test obtained a significant level of 0.00, there is a significant difference between the results of the pre-test and post-test. So it can be concluded that there is a significant effect between the effect oftraining zigzag run on increasing agility in male students aged 16-18 years. Keywords: Zigzag run, Agility.